Exploring authors engagement in journals with questionable practices: a case study of OMICS - Boukacem-Zeghmouri, Cherifa; Pergola, Lucas; Castaneda, Hugo (Malaysian Journal of Library and Information Science, 2023)
The paper aims to understand the context and drivers of researchers' decision to submit a manuscript to a journal with questionable practices. Using OMICS as a case study and asking authors for their views, the paper presents their profile, motivations and publishing experiences. The methodology is based on a questionnaire sent by e-mail to all authors of articles in journals published by OMICS (+2200). The authors were asked about (a) the factors that influenced their decision to submit their article; (b) their publishing experience with OMICS; (c) their level of satisfaction; and (d) whether or not they would repeat the experience. A total of 86 responses were collected and 18 e-mails were received. The analysis made it possible to add details to the profiles of authors already identified in the literature, but also allowed new and more nuanced profiles. This research extends our knowledge on the phenomenon of predatory publishing from the authors' feedback and provides a better understanding of the socio-economic, psychosocial and geo-political conditions that drive researchers' decisions to submit their work to a possible, potential, or probable predatory journal. At the same time, it reveals some of the strategies used by OMICS to persuade authors to submit their papers. The findings will help to inform institutional policies that seek to put in place efficient measures to combat predatory publishing.